Antologia Miłosza - Olejniczak, Jósef (Postscriptum Polonistyczne, 2020)
The author of the article offers insights into the process of preparing an anthology of Czesław Miłosz’s poetry by composing a list of major challenges that either a scholar or a critic undertaking such task must face. Paradoxically, the author stresses the fact that either a mere synthesis or a complete anthology of Miłosz’s oeuvre is rendered impossible by its sheer magnitude, plurality of poetic voices, generic diversity and thematic richness. In conclusion, the author enumerates the most important features of Miłosz’s poetry, such as its unrelenting subjectivity (as in the case of the strong, subjective poetic voice, always rooted in poet’s autobiography) and numerous and persistent dichotomies: intuitive seer versus labouring artisan; mystic versus hard working rationalist; Darwinist versus naturalist; romantic versus antiromantic; detached historian versus a subject of history musing over its meaning, and last but not least, an erudite poet versus a naive, spontaneous one.